1963
DOI: 10.1677/joe.0.0260075
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Spermiogenesis, Prostate and Seminal Vesicle Development in Normal Animals With Anti-Gonadotrophic Hormone Serum

Abstract: The daily injection of anti-sheep ICSH serum (A/S) for 9 days into immature male rats (30 days initial age) not only resulted in a 79 % inhibition of testes weight gain as compared to the testes of controls injected with normal rabbit serum (NRS), but caused these organs to ascend into the inguinal canal. This was accompanied by a complete suppression of spermiogenesis in the A/S-injected animals, whereas the testes of all NRS-injected animals showed the presence of spermatozoa in some of the tubules.Administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
1982
1982

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 5 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Recently it has been demonstrated that the injection of antiserum to purified ovine pituitary interstitial cell stimulating hormone (ICSH) into normal immature or young adult rats will result in a marked suppression of testis and accessory organ development, associated with a significant inhibition of spermiogenesis (Hayashida, 1962). In this study it was observed that the interstitial cells in the testes of the normal rats given antiserum were as deficient as those seen in hypophysectomized control animals ; yet there was no detectable effect of the antiserum on gain in body weight or on weights of adrenals or thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been demonstrated that the injection of antiserum to purified ovine pituitary interstitial cell stimulating hormone (ICSH) into normal immature or young adult rats will result in a marked suppression of testis and accessory organ development, associated with a significant inhibition of spermiogenesis (Hayashida, 1962). In this study it was observed that the interstitial cells in the testes of the normal rats given antiserum were as deficient as those seen in hypophysectomized control animals ; yet there was no detectable effect of the antiserum on gain in body weight or on weights of adrenals or thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization against LHRH will lead to decreased pituitary gonadotrophin secretion, resulting in testicular atrophy (Fraser 1975(Fraser , 1980. Immunization against LH also causes testicular atrophy (Dym & Madhwa Raj 1977;Faulkner et al 1975;Hayashida 1963;Talaat & Laurence 1971). However, immunization against LHRH or LH will result not only in an interference with spermatogenesis but also with the testosterone production which is required for the maintenance of male sex characteristics including accessory sex gland function, libido and potency.…”
Section: Lhrhorlhmentioning
confidence: 99%